O37 M5049, a novel potent and selective inhibitor of toll-like receptors 7 and 8 (TLR 7/8). (23rd March 2020) - Sherer, Brian; Bender, Andrew T; Pereira, Albertina; Reissig, Sonja; Haselmayer, Philipp; Okitsu, Shinji L; Tzvetkov, Evgeni; Przetak, Melinda; Morse, Noune Tahmassian; Vlach, Jaromir
Abstract : Background: TLR 7/8 are transmembrane receptors that recognize single-stranded RNA. In humans, TLR7 is mainly expressed in B cells and plasmacytoid dendritic cells and its activation stimulates antibody production and secretion of cytokines including type I interferon (IFN). Activation of TLR8 in myeloid cells leads to cytokine production, and activation of antibacterial host–protective mechanisms (eg, neutrophil NETosis). Aberrant activation of TLR 7/8 is potentially pathogenic and linked to progression of certain autoimmune diseases such as SLE. Thus, inhibition of TLR7/8 may be an effective treatment approach for SLE. Methods: Compounds were prepared and optimized for potency by testing them in TLR7/8-stimulated HEK 293 cells, peripheral blood mononuclear cells (PBMCs), and human whole blood. M5049 was selected as the compound with the best balance of potency, pharmacokinetic, and physiochemical properties. The pharmacokinetic and pharmacodynamic activity of M5049 was assessed in mice to determine its in vivo potency and duration of action. M5049 was also tested in mouse lupus models. Results: M5049 showed potent and selective activity in a wide range of cellular assays for inhibition of TLR7/8. M5049 inhibited R848–stimulated cytokine production in human PBMCs and whole blood, and TLR8–mediated NETosis in human primary neutrophils. In mice, M5049 showed a dose-dependent inhibition of R848–stimulated cytokine release and a long duration of action. M5049 demonstrated efficacy in suppressing disease development in the BXSB- Yaa and IFN-α accelerated NZB/W F1 mouse models of lupus. Conclusions: M5049 is a highly potent and selective inhibitor of TLR 7/8 that effectively reduces lupus pathogenesis in mice. M5049 may have potential to treat autoimmune diseases such as SLE in humans.